2016
DOI: 10.1007/s11266-016-9768-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Contemporary Challenges to INGO Legitimacy: Integrating Top-Down and Bottom-Up Perspectives

Abstract: In recent years, INGO legitimacy has been subject to growing scrutiny from analysts and practitioners alike. Critics have highlighted a backlash against INGOs in the Global South, a growing mismatch between INGO capacities and contemporary global challenges, and diminishing support for norms such as democracy and human rights that underpin INGOs' work. Although these problems have attracted significant attention within the academic literature, this article argues that existing explorations of INGO legitimacy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 66 publications
(69 reference statements)
1
27
0
Order By: Relevance
“…INGOs are NGOs which are operating in multiple countries and sectors, like development or environmental (Walton et al 2016). Clark evaluated the motivations of the INGO Charter members for joining, the perceived benefits of membership and the members' attitude on the Charter's efficacy.…”
Section: Voluntasmentioning
confidence: 99%
“…INGOs are NGOs which are operating in multiple countries and sectors, like development or environmental (Walton et al 2016). Clark evaluated the motivations of the INGO Charter members for joining, the perceived benefits of membership and the members' attitude on the Charter's efficacy.…”
Section: Voluntasmentioning
confidence: 99%
“…This process involves managing the delicate tension between seeking legitimacy from 'above' (e.g. INGO headquarters, donors and the broader global health field) and from 'below' (acceptance by national policy makers, civil society organisations or the population in the countries where they work) (Walton, Davies, Thrandardottir, & Keating, 2016). We have suggested that they seek legitimacy and, in turn, policy influence by leveraging resources of various kinds (Asad & Kay, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…They may also have political legitimacy in their own right. The existing literature on civil society legitimacy is primarily focused on the legitimacy of organisations; either nongovernmental organisations (NGOs) (Atack 1998;Edwards 1999;Brown 2001;Lister 2003;Brown and Jagadananda 2007;Walton 2008Walton , 2013 or international NGOs and transnational civil society networks (Brown 2008;Walton et al 2016). Several definitions of organisational legitimacy exist within the literature, the most prominent of which is that of Suchman, who defines it as 'a generalised perception or assumption that the actions of an entity are desirable, proper or appropriate within some socially constructed system of norms, values, beliefs and definitions ' (1995: 574).…”
Section: Civil Society Legitimacymentioning
confidence: 99%
“…They argue that an organisation can generate legitimacy through improving its performance, building stronger relationships with its constituencies, and increasing its transparency. Walton et al (2016) argue that these definitions tend to 'view legitimacy challenges in terms of technical deficiencies'. Critics argue that the focus on organisational accountability, performance and representativeness within these technical and practitioner perspectives often obscures much deeper and more political questions about legitimacy, and neglects the ways in which legitimacy is constructed and reproduced (Lister 2003;Walton 2013).…”
Section: Civil Society Legitimacymentioning
confidence: 99%